Development of an adjustable-motorized wheelbarrow / Muhammad Syahrin Suhaimi and Wan Muhammad Syahmi Wan Fauzi - Suhaimi, Muhammad Syahrin; Wan Fauzi, Wan Muhammad Syahmi (School of Mechanical Engineering, 2022)
The evolution of wheelbarrows is evolving rapidly than a few centuries before. However, the evolution is not too drastic nowadays because the demand in high tech wheelbarrows is not as high as the demand in other technology but there are still some companies that take this opportunity to create a wheelbarrow supported with modern technology like motor, engine, and so on. However, not everyone can afford to buy the wheelbarrow because of its high price. So, to increase the total users for the high tech wheelbarrow, the final year project has been done. Final Year Project (FYP1) is an adjustment and improvement of the product that already exists. The concept design and fabrication have to be done. The final product should be able to work functionally to show that this FYP project is a success.